Foreign Language Learning Strategies and Consecutive Interpreting Achievement: An Exploratory Study on Taiwanese Interpreting Students - Chiang, Yung-Nan; Villarreal, Daniel (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Although it has been frequently noted that interpreting students’ command of their working languages has not been solid enough to meet the challenge of interpreting, especially the challenge of interpreting from an A language to a B language, there has been no empirical research into whether their B language learning strategies are related to their interpretation achievement. This exploratory study filled this gap in the literature by investigating the relationship between foreign language (English) learning strategies and consecutive interpreting achievement among a group of undergraduate interpreting students in Taiwan. The participants’ learning strategies were assessed by Oxford’s Strategy Inventory for Language Learning (SILL), while their achievement was measured by their semester grades in Mandarin-English interpreting classes. Descriptive statistics and correlation analyses were used to analyze the data. The results showed that learning strategies had significant positive correlations with interpreting achievement, regardless of whether the SILL was analyzed in terms of the overall scale, its subscales, or its individual items. Based on the results, implications for offering learning strategies training to students are discussed and directions for future research are suggested.